PENGARUH MODIFIKASI TIMER PADA PENGENDALI ROLLER MIXER - Fitri Apriyulida (JURNAL MUTIARA ELEKTROMEDIK, 2017)
Roller mixer is a tool used to mix blood to achieve a homogeneous situation to avoid blood lysis, air bubbles, blood clots that can clog tool hematologi analyzer. tool is active at that time then the lcd will initialize and select the setting time 1-5 minutes. and the speed of 35 or 45 rpm, after the setting process is completed edta tube can be placed on the mixer roller. setting the assembly timer then the motor stops spinning and buzzer will sound as a marker of the completed process and the blood sample has been homogeneous. Based on measurements that have been done tolerance for speed measurement using tachometer given the tolerance range of 10%, motor voltage measurement using digital multimeter given 5% tolerance range. Keywords: Roller mixer, Homogen, Tolerance, lysis, edta, buzzer